2015
DOI: 10.1007/s11695-015-1932-z
|View full text |Cite
|
Sign up to set email alerts
|

Improved Muscle Mitochondrial Capacity Following Gastric Bypass Surgery in Obese Subjects

Abstract: Six months after gastric bypass surgery, the mitochondrial capacity for coupled, i.e., ATP-generating, respiration increased, and the P/O ratio improved. Uncoupled respiration was not enhanced to the same extent. This could partly explain the decreased basal metabolism and the reduced inclination for weight loss during energy restriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
3
12
0
1
Order By: Relevance
“…In this study, we observed that FCCP-induced maximal respiration was compromised in myotubes established from severely obese humans but did not improve following RYGB surgery. These data are in agreement with previous reports showing that reduced mitochondrial respiratory capacity was imprinted in skeletal muscle cells derived from severely obese humans [33][34][35][36][37] and RYGB surgery was not able to reverse it 34,[38][39][40] . This observation, along with improvements in mitochondrial network morphology and dynamics protein Drp1 activation at 7-months after RYGB, suggests that alterations in mitochondrial dynamics may precede improvements in mitochondrial respiratory capacity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we observed that FCCP-induced maximal respiration was compromised in myotubes established from severely obese humans but did not improve following RYGB surgery. These data are in agreement with previous reports showing that reduced mitochondrial respiratory capacity was imprinted in skeletal muscle cells derived from severely obese humans [33][34][35][36][37] and RYGB surgery was not able to reverse it 34,[38][39][40] . This observation, along with improvements in mitochondrial network morphology and dynamics protein Drp1 activation at 7-months after RYGB, suggests that alterations in mitochondrial dynamics may precede improvements in mitochondrial respiratory capacity.…”
Section: Discussionsupporting
confidence: 93%
“…Although mitochondrial uncoupled maximal respiration was not changed after RYGB surgery, it is important to point out that the results from our study does not rule out other improvements related to mitochondrial function. It has been reported that ADP-stimulated State III respiration was improved after weight loss surgery 34,38,39 . Thus, future studies should seek to use more comprehensive approaches to assess mitochondrial function in primary myotubes from RYGB patients.…”
Section: Discussionmentioning
confidence: 97%
“…Another longitudinal study in the same clinical population as the present study has recently been published . In that study, the patients were followed 6 months post‐operatively and the authors reported an increased state 3 respiration and P/O ratio following surgery.…”
Section: Discussionmentioning
confidence: 73%
“…On the other hand, the effects on mitochondrial function seem to be dependent of intervention time, since after 6 months of endurance training increases genes expression entails in oxidative phosphorylation, but mitochondrial mass and function were not assessed . Also, the improved mitochondrial respiration may be related by weight loss, as was found after 18 months bariatric surgery, as well as other studies after bariatric surgery found to increase mitochondrial coupling and ATP generation in skeletal muscle, a known effect of physical training in this tissue . Studies in skeletal muscle have shown that mitochondrial respiration is lower in individuals with obesity compared to normal weight ones .…”
Section: Discussionmentioning
confidence: 95%